Thursday Night Football's impact on all-cause injuries in NFL players during 2012 – 2017. Issue 3 (3rd July 2019) - Baker, Hayden P.; Young-Hoon Lee, Kenneth; Dayton, Steven R.; Terry, Michael; Tjong, Vehniah K.
ABSTRACT: Objectives: This study sought to determine whether shortened recovery periods between regularly scheduled Sunday NFL games and Thursday Night Football games significantly increased the incidence of injury in NFL players. Methods: NFL injury reports and injury reserve data were collected for every NFL player, on all 32 NFL teams, for each week during the regular season, for the 2012–2013, 2013–2014, 2014–2015, 2015–2016, and 2016–2017 NFL seasons. Injuries were defined as any reported injury, not previously documented in an injury report prior to said injury. Calculated injury rates per 1000 athletic exposures for Sunday and Monday night games versus Thursday night games was used to generate relative risk of injury using 95% confidence intervals. Results: The all-cause injury rate during NFL Sunday and Monday Night Football games was found to be 7, 598 per 1000 athletic exposures, while the all-cause injury rate during Thursday Night Football games was found to be 6, 072 per 1, 000 athletic exposures. The relative risk of injury during Thursday Night Football games was calculated to be 0.97 compared to Sunday and Monday night games. Therefore, the rate of injury during Thursday Night Football games was significantly less than the rate of injury during Sunday and Monday night games, despite the lack of additional recovery time. Conclusion: This study suggests that eliminating Thursday Night Football is unlikely to improve the statistical injury rate among NFL players.